2007
DOI: 10.1055/s-2006-921579
|View full text |Cite
|
Sign up to set email alerts
|

Neugeborenenhypothyreosescreening in Deutschland. Retrospektive Analyse der Entwicklung von betroffenen Kindern am Beispiel des Bundeslandes Hessen

Abstract: The screening for hypothyreosis is well established in Hessen concerning tracking, organisation and analysis. There are short comings concerning the follow ups of children with suspicions findings, which shall be overcome by creating a new position. The long-term-follow-up according to the guidelines of the "Arbeitsgemeinschaft Pädiatrische Endokrinologie" is of central interest. Furthermore compliance is improved by regular personal counselling with the parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
0
0
3
Order By: Relevance
“…Similarly, in the study of Bezen et al (19), etiological distribution was evaluated among the cases with permanent CH; rate of dysgenesis was found to be 52.2% (34.8% hypoplasia, 17.4% ectopia) and rate of dyshormonogenesis was found to be 47.8% in patients. Although there are many studies which have reported that the rate of dysgenesis is high (20,21), there has been an increase in the rate of dyshormonegenesis in recent studies in accord with our findings (19,22). An Italian national study conducted by Olivieri et al (12) reported the rate of dysgenesis in CH cases was 82% between years 1987 and 1998 although it decreased significantly compared to the previous period with a rate of 58% between years 1999 and 2006 due to significant chnages in the screening protocols used in Italy and, the authors speculate, the increased survival of many more premature infants.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in the study of Bezen et al (19), etiological distribution was evaluated among the cases with permanent CH; rate of dysgenesis was found to be 52.2% (34.8% hypoplasia, 17.4% ectopia) and rate of dyshormonogenesis was found to be 47.8% in patients. Although there are many studies which have reported that the rate of dysgenesis is high (20,21), there has been an increase in the rate of dyshormonegenesis in recent studies in accord with our findings (19,22). An Italian national study conducted by Olivieri et al (12) reported the rate of dysgenesis in CH cases was 82% between years 1987 and 1998 although it decreased significantly compared to the previous period with a rate of 58% between years 1999 and 2006 due to significant chnages in the screening protocols used in Italy and, the authors speculate, the increased survival of many more premature infants.…”
Section: Discussionsupporting
confidence: 91%
“…З метою ранньої діагностики УГ у ба-гатьох країнах світу проводиться неонатальний скринінг [9]. Початковим пріоритетом неона-тального скринінгу на УГ є виявлення всіх форм первинного гіпотиреозу.…”
Section: № 3 2017unclassified
“…В основі більшості випадків (70-85 %) УГ ле-жать уроджені аномалії розвитку ЩЗ, значно рідше (5-20 %) -дисгормоногенез (уроджені дефекти біосинтезу гормонів включають порушення захвату, органіфікації, зв'язування йоду, зміни активності дейодиназ і аномалії синтезу, накопичення та ви-вільнення тиреоглобуліну (ТГ)) [9].…”
Section: № 3 2017unclassified
“…Gefahndet wird in Deutschland zurzeit nach nur zw ö lf unterschiedlichen endokrinen und metabolischen Diagnosegruppen, deren Krankheitswert gesichert ist und f ü r die wirksame Behandlungsverfahren verf ü gbar sind [22] . Trotz der nachgewiesenen Effi zienz einer schon in den ersten Lebenstagen einsetzenden Fr ü htherapie bedarf es der regelhaften Ü berpr ü fung der Langzeitergebnisse und Adaptierung der Betreuung, wie landesweite Nachuntersuchungen f ü r das Krankheitsbild der konnatalen Hypothyreose belegen [14] . Die vollst ä ndige soziale Reintegration der Patienten ist das Ziel, und deshalb bedarf es in der Diagnostik und Behandlung der f ä cher ü bergreifenden horizontalen und vertikalen Vernetzung bis in das Erwachsenenalter.…”
unclassified